ANEMIA STATUS AMONG PREGNANT WOMEN DELIVERING AT VINMEC TIMES CITY INTERNATIONAL GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the current status of anemia during pregnancy among women delivering at Vinmec Times City International General Hospital in 2024-2025.Methods: A retrospective cross-sectional study was conducted on 2572 pregnant women who delivered at Vinmec Times City International General Hospital from July 1, 2024 to June 30, 2025.Results: The average age of pregnant women was 33.8 ± 4.6 years. The prevalence of anemia in the first, second, and third trimesters was 5.8%, 23.6%, and 15.3%, respectively, with an overall prevalence of 15.4%. No cases of severe anemia were recorded, mild anemia was the most common condition (82%). Anemia was most common in women aged 25 to under 35 years (16.4%) and lowest in those aged 35 to under 40 years (13.9%). There were statistically significant associations between anemia and parity, as well as serum ferritin levels (p < 0.05).Conclusions: The prevalence of anemia was 15.4%, predominantly mild, with the highest rate observed in the second trimester. Anemia was associated with parity and ferritin levels. These findings highlight the important role of iron stores and the need for timely screening and micronutrient supplementation during pregnancy.
Keywords: Anemia, pregnancy, ferritin, prevalence.